Sucesivos aportes al concepto de adolescencia en la obra freudiana (2014)
ABSTRACT: A follow-up work is established to the specific reflections made by Freud around adolescence, trying to determine the corresponding theoretical context in each period. It is found that successive theoretical contributions are framed in three moments of Freud’s work: the first psychopathological explanations of neurosis in the late nineteenth century, the rethinking that induces the development of the theory of infantile sexuality, and finally, the revaluation of the etiological role of the Oedipus Complex, associated to maintaining the notion of après-coup (Nachträglichkeit). This way, the profile is not only identified and outlined from the more general theories underlying the dispersed propositions, but some of these statements are recognized as essential contributions to the contemporary conception of adolescence.